Implikasi Pasal-Pasal Pelindung (The Trips Safeguards) dalam UU Paten Indonesia: Kritik, Evaluasi dan Saran dari Perspektif Akses terhadap Obat yang Murah dan Terjangkau - Tomi Suryo Utomo (Fakultas Hukum Universitas Islam Indonesia, 2007)
The discussion about access to essential medicine issues nowadays cannot be separated from the TRIPS Agreement. The TRIPS Agreement is important because one of its provisions (Article 27) deals with the protection of pharmaceutical patent which has a great relevance to access to essential medicine issues, such as affordability of drugs. The TRIPS Agreement also regulates a series of policies called the TRIPS safeguards, such as parallel imports, bolar provision, compulsory license and government use that can minimize and manage the impact of pharmaceutical patent protection on access to essential medicines. Indonesia’s patent law includes the safeguards provided by the TRIPS Agreement, such as parallel importation, bolar provisions, compulsory licenses and government use. However, several areas need to be improved so that the safeguards can be effectively used to manage the impact of pharmaceutical patent protection on access to medicines. Indonesia should seek a balance between pharmaceutical patent protection and use of policies and strategies that are essential for its public welfare.